PERAN POLRI DALAM MENGEMBANGKAN KERJASAMA INTERNASIONAL GUNA PENANGGULANGAN KEJAHATAN NARKOTIKA YANG TERORGANISIR - Andi Rian Djajadi; Suhaidi Suhaidi; Mahmul Siregar; Muhammad Hamdan (USU LAW JOURNAL, 2014)
ABSTRACT The crime of drug abuse and drug trafficking not only become the problem of  certain country but also become inter-states and international matter. It has wide organizational network so police need to handle it by performing multilateral, bilateral and regional coopertaion. Obviously, international cooperation which exist today is still oriented to routine annual meetings among the Asian countries, concerning international crime (SOMTC) or cooperation among the police in bilateral, regional and international level (ASEANAPOL, INTERPOL etc), with the target of mission cooperation in combating international crime as a whole, without specifically talks about the issues of international narcotics crime and it syndicates technically and how to handle it. International instrument in combating organized narcotics crime is by international convention which is ratified in the national law and in the bilateral and regional regulations. The role of the police in developing international cooperation is by taking proactive measures in its dandling, but in its implementation faces some obstacles such as the cooperation is only about on agreement, and mutual assistance is done without intensifying operational cooperation. This is because of the lack of the willingness of the state that is requested to help does not handle the perpetrators. The problem is that there is no technical formula among the nations in combating the perpetrators who are accused of commiting narcotics crime so that there is no task force action from the police of each nation. Besides that, there is no cooperation among the nations concerning the tracing and the confiscation of the assets of the organized narcotics crime perpetrators among the nations. The attempt to develop intensive cooperation should involve all nations.